1994
DOI: 10.1300/j052v13n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Nutrition Education and Physical Fitness Training Program in Lowering Lipid Levels in the Black Elderly

Abstract: A multidisciplinary nutrition education and fitness training program was tested for its effectiveness in lowering lipid profiles of elderly clients through dietary modification and exercise. The program served 31 free-living, predominantly female, black elderly aged 56-88 years. Dietary, anthropometric, biochemical, and fitness assessments were performed before and after the 10-week, biweekly program. Significant decreases (p < 0.05) were seen in waist circumference, total cholesterol (TC), low-density lipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…Just as they functioned for recruitment, local churches were also commonly used for intervention delivery and data collection [24, 35, 38, 40, 49, 55, 56, 63, 69–71, 78, 85]. Other underrepresented-specific sites for intervention delivery included community settings [41, 58, 86] such as underrepresented group member owned or frequented fitness centers [22, 28, 55, 57, 71], and hospitals serving underrepresented communities [37, 41, 54, 65].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Just as they functioned for recruitment, local churches were also commonly used for intervention delivery and data collection [24, 35, 38, 40, 49, 55, 56, 63, 69–71, 78, 85]. Other underrepresented-specific sites for intervention delivery included community settings [41, 58, 86] such as underrepresented group member owned or frequented fitness centers [22, 28, 55, 57, 71], and hospitals serving underrepresented communities [37, 41, 54, 65].…”
Section: Resultsmentioning
confidence: 99%
“…For example, walking may not be an acceptable form of exercise in the Latino community because it is viewed as indicative of low socioeconomic status [85]. A number of interventions in the project sample incorporated culturally specific forms of PA [19, 23, 49, 53, 65, 66, 68, 70, 71, 77, 80, 91]. One dance intervention integrated physical, mental, and spiritual health as common in the underrepresented group [70].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doshi et al 18 , por sua vez, ao avaliarem uma intervenção educativa entre idosos negros, após dez semanas com orientação nutricional (duas vezes por semana), acompanhada de atividade física, não encontraram diferença entre o valor energético da dieta inicial e aquela posterior à intervenção. Essas alterações no consumo alimentar estão em consonância com os achados de Constants et al 19 que, ao desenvolverem intervenção educativa em UATI, na França, também obtiveram um resultado positivo.…”
Section: I S C U S S ã Ounclassified
“…Conversely, exercise training can reduce TG and LDL-C and increase HDL-C. Following 10 weeks of aerobic exercise training, Doshi et al reported an 8% reduction in cholesterol/HDL-C ratio in older AAs, independent of changes in body composition [136]. Conversely, a study in South African Blacks found no significant change in HDL-C levels after exercise training [137].…”
Section: Apolipoprotein E Gene As a Modifier Of Ad Riskmentioning
confidence: 99%